Ventriculo-atrial shunt with occlusion of the internal jugular vein: operative experience and surgical technique - Silvia Tatiana Quintero; Felipe Ramirez-Velandia; Andres Felipe Hortua Moreno; Lina Vera; Paula Rugeles; Rafael Augusto Azuero Gonzalez (Chinese Neurosurgical Journal, 2024)
Abstract Background Ventricular shunts are one of the most frequent techniques used for the management of hydrocephalus. The ventriculoperitoneal shunt (VPS) is the most commonly performed procedure, and the ventriculoatrial shunt (VAS) is the second option in most medical centers. The main objective of this study is to introduce and describe a surgical approach for VAS outlining our experience and comparing it with traditional shunting techniques. Methods In this retrospective cohort comparison study, we included patients with hydrocephalus treated with a surgical procedure between January 2010 and February 2021 at a single academic institution. We categorized the procedures into two groups: patients with VPS and conventional VAS grouped together into the conventional technique (CT) group, and the second group was patients with whom we performed VAS with complete internal jugular vein occlusion (IJVOT). We compared the surgical time, postoperative complications, and occurrence of shunt failure among the groups by performing univariate analysis using the Fisher exact test. Results Out of the 106 patients included in the analysis, IJVOT was performed in 66 patients, and CT in 40 patients. The median surgical time was 60 min (IQR 60–90) for IJVOT versus 100 min (IQR 60–120) for CT (p < 0.01). In the follow-up a month after the procedure, 83.3% of patients with IJVOT and 62.5% of patients with CT did not require shunt removal or shunt revision (p < 0.01). Shunt revision rates were 12.5% and 1.5% for CT while 1.5% and 2.5% for IJVOT at 1 and 6 months after the procedure. Conclusion Our findings demonstrate that VAS with IJVOT is a safe method that exhibited shorter surgical times and outcomes comparable to CT. However, since the present study represents the first cohort evaluating IJVOT, it is imperative to conduct larger prospective studies, along with clinical trials, to fully explore and establish efficacy, long-term outcomes, and an in-depth comparison among shunting techniques.